Políticas afirmativas no Brasil: cotas raciais nas universidades federais brasileiras (2004-2018) - Rodrigues, Josefa Neves (2022)
This work aims to analyze the implementation of Affirmative Action Policies in Brazilian federal universities. These policies are decisions of university councils, which act in accordance with the regional culture. It seeks to identify, analyze and explain the different admission proposals adopted by different federal universities regarding the racial quota system and the results achieved by them in terms of access to different courses. The eleven universities selected, from the five regions of the country, were the first to adopt the racial quota system, even before Law 12.11.711/2012, which regulated affirmative policies and determined the distribution of vacancies according to IBGE population percentages. The 2004-2018, time frame follows from this. In the light of authors such as Adorno, Arendt, Bourdieu, Candau, Carvalho, Dávila, Fernandes, Foucault, Hall, Hasenbalg, Gomes, Guimarães, Munanga and Santos, the philosophical and legal foundations of the measures adopted by federal universities in the face of inequality of access to Brazilian public higher education, a reflection of our society, marked by diversity and inequality. We sought to identify - until 2018 - the process of distributing Quotas for admission to undergraduate courses considered to have a greater possibility of social ascension - in which the highest incidence of fraud was found. It was identified that the system of Affirmative Action Policies played a decisive role in the inclusion of black, brown and indigenous students in federal universities, but without achieving in higher education the proportionality of blacks and indigenous people in society